Philosophical Analysis of Problem-Based Learning Model in Sociology Learning: Ontological, Epistemological, and Axiological Perspectives - Ilham, Wahyu; Fatimah, Siti; Anwar, Syafri (LANGGAM: International Journal of Social Science Education, Art and Culture, 2026)
This study analyzes the Problem-Based Learning model in Sociology Learning through an educational philosophy approach covering ontological, epistemological, and axiological dimensions. Through the literature study method, this study aims to analyze how the PBL model reflects the ontological dimension in sociology learning, knowledge is constructed epistemologically through PBL, and axiological values that emerge from the application of PBL. The results of the literature study show that ontologically, PBL reflects real and contextual social reality as a source of problems to be analyzed. Epistemologically, PBL emphasizes the construction of knowledge through the process of scientific inquiry, orientation of students to problems, organizing students for learning, guiding students in individual and group investigations, improving and presenting the results of student work, and analyzing and evaluating the problem-solving process. Meanwhile, axiologically, PBL instills the values of creativity, critical thinking, independent learning, motivation, responsibility for learning, collaboration, and group cooperation. Thus, the application of the PBL model in sociology learning has a strong relationship between the dimensions of ontology, epistemology, and axiology. The limitation of this study is the lack of direct empirical validation. Therefore, further research is recommended to test the implementation of PBL through classroom action research or experiments to obtain concrete evidence regarding its effectiveness.